The Effectiveness of LASIK Surgery Process Education and Guided Imagery on Anxiety and Emotional Self-Regulation among Female LASIK Candidates - Khodaverdi Gharachehdaghi, Anahita; Bazzazian, Saeideh (Journal of Ophthalmic and Optometric Sciences, 2025)
Purpose: To examine the effectiveness of laser assisted in situ keratomileusis (LASIK) surgery process education and positive guided imagery in reducing anxiety and enhancing emotional self-regulation among female LASIK candidates. Patients and Methods: The statistical population for this study consisted of female candidates for LASIK surgery at the operating room of Negah Eye Hospital, Tehran, Iran. A total of 30 participants were selected using convenience sampling over the course of one month and randomly assigned to either an experimental or a control group, with 15 participants in each group. Both the experimental and control groups completed the Athens Physical Activity Questionnaire (APAQ) and the Gross and John Emotion Regulation Questionnaires before the intervention. After completing these questionnaires, the experimental group received comprehensive training on the LASIK procedure, including detailed explanations of the surgical steps, followed by positive mental imagery exercises. The control group received only the standard preoperative instructions. Thirty minutes later, the APAQ was administered again to both groups, and the Gross and John Emotion Regulation Questionnaire was re-administered after surgery. Results: LASIK surgery process education combined with positive guided imagery significantly reduced preoperative anxiety (P = 0.035) and improved postoperative emotional self-regulation (P = 0.026) among female LASIK candidates. Conclusion: Education on the LASIK procedure and guided mental imagery effectively reduces preoperative anxiety and enhances postoperative emotional self-regulation among female patients undergoing this procedure.